PGV-1 is a Potent Antimitotic Agent - Widaryanti, Barinta; Da’i, Muhammad; Kawaichi, Masashi (Indonesian Journal of Biotechnology, 2008)
Carcinogenesis may resulted from the malfunctioning of programmed cell death. Most of the anticancer drugs incurrent use induce apoptosis in susceptible cells. The fact that disparate agent interacting with different targets seemto induce cell death through some common mechanisms suggest that anticancer activity is determined by the abilityof inhibiting cell growth. Pentagamavunon-1 (PGV-1) is one of the curcumin analogues which showed to havepotency in inhibiting proliferation of T47D human breast carcinoma cells. The effects on T47D cells growth isassociated with cell cycle arrest in G2/M phase at the concentration of 2.5 ?M, followed by hyperploidy. The data onpolymerization assay, indicated that PGV-1 interact with tubulin in different manner from taxol. PGV-1 inhibittubulin polymerization on cell culture while taxol stabilized tubulin polymerization. Immunostainning data onPGV-1 treated cells showed slightly tubulin condensation, while taxol treated cells showed tubulin condensationdistinctly at 12 minutes after releasing from depolymerizing agent.In conclusion, PGV-1 represent a new microtubule inhibitor and has the potential to be developed for antimitoticdrugKey words: Pentagamavunon-1, T47D, tubulin